Hiperrealitas Musik dalam Peluang Pedagogis di Era Disrupsi : Penelitian - Bayu Aji Wicaksono; Setyo Yanuartuti; Warih Handayaningrum (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This article examines the transformation of music's meaning and function in the digital disruption era through the lens of Jean Baudrillard’s hyperreality framework. Algorithmically curated digital music such as "Focus Mode" or "Lo-fi to Study To" playlists has shifted from being an aesthetic expression to becoming a simulated affective instrument designed to regulate mood and productivity. This phenomenon not only reflects the decline of artistic depth but also opens new pedagogical opportunities. Using a qualitative-critical approach based on literature review and discourse analysis, the study explores how simulated music can function as a pedagogical tool, both as a means to shape learning atmospheres and as an object of cultural critique. The findings reveal that, when used reflectively, digital music can enhance affective awareness, media literacy, and aesthetic meaning among learners in an age dominated by signs and algorithms. In this context, music is no longer merely background sound but a contested space between simulation and consciousness. Therefore, music education in the digital era must be designed not just for convenience but to cultivate critical reflection on how sound mediates learning experiences and shapes the subjectivity of the digital generation.